Effect of Cricket Meal (Gryllus bimaculatus) on Production and Physical Quality of Japanese Quail Egg - D. Permatahati; R. Mutia; D. A. Astuti (Faculty of Animal Science, Bogor Agricultural University, 2019)
Feed cost contributes 80% of the total cost of production in quails. The utilization of cricket meal as a protein source can be a solution to reduce feed costs. The cricket has a high nutritive value, especially protein content, and is one of potential insects to be used as a source of alternative protein to replace fish meal in animal diet. This study aimed to evaluate the effect of cricket meal on the production and physical quality of japanese quail egg (Coturnix coturnix japonica). The experiment used 200 five-week-old female quails with an average body weight of 125.4 g. The completely randomized design (CRD) was employed for the experiments with 5 treatments and 4 replications (10 birds per replication). The dietary treatments were T0: diet without cricket meal, T1: diet containing 2% cricket meal to replace 25% of fish meal, T2: diet containing 4% cricket meal to replace 50% of fish meal, T3: diet containing 6% cricket meal to replace 75% of fish meal, and T4: diet containing 8% cricket meal to replace 100% of fish meal. Results revealed that utilization of cricket meal in the quail ration significantly increased egg production (P<0.05) and positively affected physical quality of quail eggs, such as egg weight, egg white weight, eggshell weight, and yolk score. It can be concluded that cricket meal can partially or fully replace fish meal in the diet of layer quails.